Information Systems Project Risk Assessment: Expert Approach - Chernysheva T. Yu. Tatiana Yurievna; Gnedash E. V.; Zorina T. Y.; Lenskaya N. V. (Management and Economic Aspects Development of Enterprises, 2014)
Title screen